Microbiological and clinical characteristics of cryptococcemia: a retrospective analysis of 85 cases in a Chinese hospital. (4th September 2019) - Fu, Yiqi; Xu, Min; Zhou, Hua; Yao, Yake; Zhou, Jianying; Pan, Zhijie
Abstract: Cryptococcemia is a life-threatening fungal infection. Sometimes, it is hard to diagnose. The studies to describe the characteristics of cryptococcemia specifically were limited. We performed this retrospective analysis in a Chinese hospital during 2002–2015, including 85 cryptococcemia cases and 52 Cryptococcus spp. isolates. The species, mating type, antifungal susceptibility and multilocus sequence typing of Cryptococcus spp. were determined. C. neoformans var. grubii MATα of sequence type (ST) 5 is the representative strain of cryptococcemia, accounting for 51 isolates. The MIC50/90 values were 0.5/0.5, 1.0/1.0, 2.0/4.0, ≤0.06/0.25, and ≤0.06/≤0.06 μg/ml for amphotericin B, flucytosine, fluconazole, itraconazole, and voriconazole, respectively. Cryptococcemia was the first diagnostic proof of cryptococcosis in 37 patients (43.5%, 37/85). Compared with the patients initially diagnosed of cryptococcosis in other sites (mainly cerebrospinal fluid), the patients firstly diagnosed by blood culture had prolonged time from admission to diagnosis of cryptococcosis (9 days vs. 2 days, P < .001) and higher 30-day mortality (54.1% vs. 20.8%, P = .003), while fewer symptoms of meningitis (45.9% vs. 100%, P < .001). For the patients receiving lumbar puncture, the occurrence of meningitis was similar between the patients firstly diagnosed by blood culture and those firstly diagnosed in other sites (94.1% vs. 100%, P = .26). However, the patients first diagnosed by blood culture had lower baseline intracranial pressure (250 mm H2 O vs. 342.5 mm H2 O, P = .001). In conclusion, patients with cryptococcemia as the first diagnostic proof of cryptococcosis usually had neglected subtle symptoms of meningitis, which may result in delayed diagnosis and catastrophic outcome.